Sarcasm in Sentiment Analysis of Indonesian Text: A Literature Review - Sherly Christina (Universitas Palangka Raya, 2019)
Social media, blogs and online groups become a forum that makes is easy for the Indonesian people to express their opinions, suggestions, complaints and even criticisms of a subject liberally. Sentiment analysis is a method for classifying positive, neutral, and negative polarity of the opinions that expressed by the internet users. Sarcasm is one of the challenges to classsifying the sentiments of an opinion. This research is a literature review to examine several studies to find out the methods for detecting sarcasm and to know the effect of sarcasm on the sentiment classification accuracy. The result of this literature review can be used as a reference for developing the sarcasm detection methods.